Public space design of knowledge and innovation spaces: learnings from Kelvin Grove Urban Village, Brisbane - Surabhi Pancholi; Tan Yigitcanlar; Mirko Guaralda (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
The era of knowledge-based urban development has led to an unprecedented increase in mobility of people and the subsequent growth in new typologies of agglomerated enclaves of knowledge such as knowledge and innovation spaces. Within this context, a new role has been assigned to contemporary public spaces to attract and retain the mobile knowledge workforce by creating a sense of place. This paper investigates place making in the globalized knowledge economy, which develops a sense of permanence spatio-temporally to knowledge workers displaying a set of particular characteristics and simultaneously is process-dependent getting developed by the internal and external flows and contributing substantially in the development of the broader context it stands in relation with. The paper reviews the literature and highlights observations from Kelvin Grove Urban Village, located in Australia's new world city Brisbane, to understand the application of urban design as a vehicle to create and sustain place making in knowledge and innovation spaces. This research seeks to analyze the modified permeable typology of public spaces that makes knowledge and innovation spaces more viable and adaptive as per the changing needs of the contemporary globalized knowledge society.
Keywords: 650; Knowledge and innovation space; Place making; Contemporary public spaces; Knowledge-based urban development; Knowledge worker; Kelvin Grove Urban Village; Brisbane: Australia